2011
DOI: 10.4081/ejh.2011.e28
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive heterochromatin polymorphisms in human chromosomes identified by whole comparative genomic hybridization

Abstract: Whole comparative genomic hybridization (W-CGH) is a new technique that reveals cryptic differences in highly repetitive DNA sequences, when different genomes are compared using metaphase or interphase chromosomes. W-CGH provides a quick approach to identify differential expansion of these DNA sequences at the single-chromosome level in the whole genome. In this study, we have determined the frequency of constitutive chromatin polymorphisms in the centromeric regions of human chromosomes using a whole-genome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Since the centromere regions that are targeted by the FISH probes are not covered by MPseq, it is unclear whether a small gain or presence of a polymorphism of these regions are present without evidence of a bona fide trisomy or whether the trisomy was present at a subclonal level below the limit of detection by MPseq (<25% for CNAs) 18 . Polymorphisms of the acrocentric chromosome 15 have also been reported 39 and are observed in FISH analysis of PCNs in our laboratory (data not shown). Discrepancies involving chromosome 15 are present in 6 of 70 cases in this study demonstrated by either a monosomy 15 FISH result with normal chromosome 15 s by MPseq or either a normal or monosomy 15 FISH result with trisomy 15 by MPseq.…”
Section: Discussionsupporting
confidence: 71%
“…Since the centromere regions that are targeted by the FISH probes are not covered by MPseq, it is unclear whether a small gain or presence of a polymorphism of these regions are present without evidence of a bona fide trisomy or whether the trisomy was present at a subclonal level below the limit of detection by MPseq (<25% for CNAs) 18 . Polymorphisms of the acrocentric chromosome 15 have also been reported 39 and are observed in FISH analysis of PCNs in our laboratory (data not shown). Discrepancies involving chromosome 15 are present in 6 of 70 cases in this study demonstrated by either a monosomy 15 FISH result with normal chromosome 15 s by MPseq or either a normal or monosomy 15 FISH result with trisomy 15 by MPseq.…”
Section: Discussionsupporting
confidence: 71%
“…Replication of centromeres is associated with chromosome fragility and double strand breaks, which may be due to the collapse of replication forks [112][113][114]. Pericentromeric and alpha satellite repeats evolve at a faster pace than the rest of the primate genome and also display length polymorphisms amongst humans, suggesting they are very prone to instability [106,[115][116][117]. Studies in fission yeast (which have different centromere sequences but similar centromeric chromatin to humans) have identified several of the replication fork restart proteins, including Smc5/6 and Brc1, as crucial to duplicating and suppressing crossover recombination within centromeric regions (for a recent review see [118]).…”
Section: Is Centromeric Repeat Instability Similar To Large-scale Micmentioning
confidence: 99%
“…Fragmentation was not observed in any of the other chromosomes that exhibit smaller regions of heterochromatic DNA. In humans, the centromeric and telomeric regions of all chromosomes along with larger portions of the 1, 9, 16, Y and second X chromosomes are heterochromatic [24]. Besides the second X chromosome, no other chromosomes are primarily heterochromatin.…”
Section: Nickel Subsulfide Is Clastogenic To Human Lung Epithelial Cellsmentioning
confidence: 99%